Assessment of quality of life of patients with leprosy treated at a tertiary care centre in western Maharashtra - Ray, Avinash Kumar; Tripathi, Swapnil; Ali, Hayder Hussein Ali; Khan, Mohammed Athif (International Journal Of Community Medicine And Public Health, 2025)
Background: Leprosy still remains an important public health problem in India. Though effective treatment is available, but delay in diagnosis and seeking treatment often results in patients presenting with deformity and disability affecting their quality of life. This study aimed to evaluate the quality of life of leprosy patients with grade-1 or above disability and to identify certain factors affecting QOL. Methods: A cross-sectional study was conducted at the Government Leprosy Hospital in western Maharashtra using the WHO quality of life assessment questionnaire, WHO-QOL (BREF). Results: In the assessment of QoL, the lowest rating was observed in the social domain, and the highest was observed in the environmental domain. Males had better QOL scores in all domains as compared to their female counterparts. The internal consistency of WHOQOL-BREF was acceptable to the facets and domains. Conclusions: Leprosy not only causes physical suffering but also impacts bodily image, leading to low confidence, ostracization from family and society, as well as economic deprivation, leading to poor quality of life.